(untitled) (Dhaka University Journal of Science, 2012)
The critical micelle concentration (CMC) of Sodium dodecyl sulfate (SDS) in water was determined from the conductance and viscosity measurement. The estimated value of CMC was found to be 0.0085 mol.L-1 at 29°C. The concentration of SDS in pre-micellar and postmicellar region of 0.005M and 0.01M, respectively were used for the volumetric measurements of Methanol, Ethanol, n-Propanol and iso- Propanol with SDS solutions. Densities of ternary mixtures of Methanol, Ethanol, n-Propanol and iso-Propanol with 0.005M and 0.01M aqueous SDS have been studied over the entire range of composition at 298.15- 323.15K with an interval of 5K except Methanol. Methanol system was studied at 298.15-308.15K due to its low boiling point. The values of excess molar volumes, VE for all the systems are negative over the entire range of composition, showing minima at 0.45 mole fraction of Methanol, 0.4 mole fraction of Ethanol, 0.25 mole fraction of n-Propanol and 0.3 mole fraction of iso-Propanol. All the systems are showing minima at aqueous SDS rich region. The VE values for the n-Propanol + aqueous SDS and iso-Propanol + aqueous SDS mixtures are slightly sigmoid, being negative at lower mole fractions (x2) and positive at higher x2 of Propanols. The excess properties (VE) data have been fitted by the least square method to the four parameter Redlich-Kister equation and the values of the parameter aj have been reported. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10351 Dhaka Univ. J. Sci. 60(1): 129-136 2012 (January)